Brucellosis associated with empyema of gallbladder [Safra kesesi ampiyemi ile seyreden akut bruselloz olgusu] - (:unkn) unknown (My University, 2006)
In 5%-10% of patients with acute cholecystitis, calculi obstructing the cystic duct are not found at surgery. Brucellosis is a rare cause of acute acalculous cholecystitis. We report a 52 year-old, previously healthy, man with brucellosis who presented with abdominal pain due to cholecystitis and empyema of gallbladder. A 52 year-old man presented with fever and abdominal pain for 3 days. The fever ranged from 57.5°C to 39°C. The abdomen was tender in the right upper quadrant regions. Complete blood count revealed a white blood cell count of 6200/mm3. The other laboratory tests were normal. Sonography revealed enlargement of spleen , thickening of the gallbladder wall and empyema of gallbladder. The blood culture grew a Gram negative rod, wich was subsequently identified as brucella. The standard tube agglutinin titer was 1:160. After rifampin and doxycycline treatment started, symptoms and signs recovered without surgical operation at the end of third day. Gall bladder empyema disappeared in control ultrasonographic examination at the end of the first week.
Keywords: Brucellosis; Cholecystitis